2020
DOI: 10.1021/acs.iecr.0c01748
|View full text |Cite
|
Sign up to set email alerts
|

Condensed-Phase Ethanol Conversion to Higher Alcohols over Bimetallic Catalysts

Abstract: The catalytic condensation of ethanol to n-butanol and higher alcohols, known collectively as Guerbet reactions, has attracted attention in recent years as ethanol becomes increasingly available as a biorenewable feedstock. Results are presented here for the continuous, condensed-phase conversion of ethanol to higher alcohols using Ni/La2O3/γ-Al2O3 catalysts and for catalysts containing a second metal (Cu, Co, Pd, Pt, Fe, Mo) in addition to nickel. Detailed characterization of the catalyst surface and bulk pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
0
15
0
Order By: Relevance
“…Yields of C 6+ -OH versus reaction temperature for catalysts described in this work and in the literature. ,,,− Abscissa value: Yields of C 6+ -OH (%). Ordinate value: reaction temperature.…”
Section: Resultsmentioning
confidence: 96%
“…Yields of C 6+ -OH versus reaction temperature for catalysts described in this work and in the literature. ,,,− Abscissa value: Yields of C 6+ -OH (%). Ordinate value: reaction temperature.…”
Section: Resultsmentioning
confidence: 96%
“…The biochemical route was supplanted by cost-efficient chemical synthesis of 1-butanol from petrochemical-derived propene via hydroformylation, but the need for sustainable liquid transportation fuels has renewed interest in biochemical approaches to the synthesis of 1-butanol . New microbial strains, as well as innovation in the fermentation setup, have significantly improved the productivity of microbial 1-butanol synthesis, but isolation of low concentrations of the alcohol from aqueous solution is both costly and energy intensive. ,,, Heterogeneous catalysts for ethanol upgrading generally require reaction temperatures of 250 °C or more to achieve suitable reaction rates, but the reduced activity is offset by the low price and recyclability of the catalyst in many of these systems. While the lack of base promoter prevents the formation of sodium acetate, other side products, such as higher alcohols, CO, alkenes, or ethyl acetate, are commonly formed alongside the desired 1-butanol product. Recently developed homogeneous ruthenium, iridium, and manganese catalysts for the Guerbet reaction of fermentation-derived ethanol can achieve high turnover numbers and high selectivity among liquid products for the formation of 1-butanol at moderate conversions. Use of base promoters, such as NaOEt, commonly result in the formation of sodium acetate alongside the desired 1-butanol product, but high catalyst activity can be achieved at temperatures at or below 160 °C.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Ni-based catalysts with a nanostructure can achieve excellent ethanol conversion and butanol selectivity under the mild reaction conditions and show excellent dehydrogenation and hydrogenation performance. 30,31 the agglomeration and leaching of active metal components, thereby improving the catalytic activity and stability of the assynthesized catalysts. Lignin is the second largest natural organic polymer in nature after cellulose, about 36.5−50 million tons every year.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al reported a porous metal oxide catalyst co-doped with copper and nickel that performed high activity and high selectivity when applied to the Guerbet coupling reaction. In addition, Ni-based catalysts with a nanostructure can achieve excellent ethanol conversion and butanol selectivity under the mild reaction conditions and show excellent dehydrogenation and hydrogenation performance. , Compared with Ni catalysts, Sn-modified Ni catalysts can effectively inhibit the cleavage of C–C or C–O bonds in ethanol. However, these generally used catalysts have drawbacks such as high loading, poor stability, metal agglomeration, and metal leaching during the reaction processes.…”
Section: Introductionmentioning
confidence: 99%